Оцінка впливу програми медико-психологічної корекції та санаторної реабілітації вагітних на стан новонароджених і перебіг їх раннього неонатального періоду - Сюсюка, Володимир Григорович; Котлова, Юлія Валентинівна; Syusyuka, V. G.; Kotlova, Yu. V. (My University, 2014)
Мета: оцінити ефективність програми медико-психологічної корекції у зниженні рівня тривожності та її вплив на стан новонароджених і перебіг їхнього раннього неонатального періоду. Пацієнти і методи. Обстежено 210 вагітних у II та III триместрах. Першу групу склали 80 вагітних із середнім і високим рівнем ситуативної тривожності, які узяли участь у комплексній програмі медико-психологічної корекції і санаторної реабілітації. Другу групу склали 57 вагітних, що відмовилися від медико-психологічної корекції та отримували лише стандартне санаторно-курортне лікування. Контрольну групу склали 48 вагітних з низьким рівнем тривожності (30 балів і менше). Індивідуально-психологічні особливості вагітних та їх психоемоційний стан оцінювали за допомогою комплексу психодіагностичних методів. Результати. Застосування програми медико-психологічної корекції вагітних на етапі санаторної реабілітації сприяло достовірному зниженню показника ситуативної тривожності у 82,5% випадків. У групі жінок, що отримували лише стандартне санаторно курортне лікування, зниження показника ситуативної тривожності спостерігалося лише у 52,6% випадків. Висновки. Проведена на етапі санаторної реабілітації медико-психологічна корекція вагітних, впливаючи на рівень тривожності, сприяє зниженню акушерських (передчасні пологи, аномалії пологової діяльності, дистрес плоду) і перинатальних ускладнень (асфіксія, неонатальна енцефалопатія, затримка росту плоду). Hypothesis of investigation - medical and psychological correction was made at the stage of sanatorium rehabilitation of pregnant women; having influence on the anxiety level the correction enables decrease of obstetrical and perinatal complications. Object of the work - is to estimate efficiency of developed and implemented medical and psychological program in decrease of anxiety level and to estimate its influence on the state of newborns and course of their early neonatal period. Group of examined women and methods of investigations. 210 pregnant women were examined in ІІ and ІІІ trimesters. Group І - is 80 pregnant women with middle and high level of the state anxiety (SA) who participated in complex program of medical and psychological correction and sanatorium rehabilitation. Group ІІ - is 57 pregnant women who refused to participate in medical and psychological correction. Control group included 48 pregnant women with anxiety level of 30 points and lower which characterizes low level of the SA. Individual and psychological features of pregnant women and their psychological and emotional state were investigated by means of set of psychological and diagnostic methods. Results of investigations and their discussion. Results of conducted investigation indicate that use of the developed and implemented program of medical and psychological correction of pregnant women at the stage of sanatorium rehabilitation enables accurate decrease of the state anxiety factor in 82.5% of cases. Group of women who refused to participate in the program and got rehabilitation under the standards of sanatorium-resort therapy, decrease of the state anxiety factor occurred only in 52.6% of cases. Conclusion. Medical and psychological correction was made at the stage of sanatorium rehabilitation of the pregnant women; having influence on the anxiety level it enables decrease of obstetric (preterm delivery, abnormalities of labour process, distress of fetus) and perinatal complications (asphyxia, neonatal encephalopathy, growth retardation of fetus).
Оценка влияния программы медико-психологической коррекции и санаторной реабилитации беременных на состояние новорожденных и течение их раннего неонатального периода
Estimation of influence of medical and psychological correction and sanatorium rehabilitation of pregnant women program on state of newborns and course of their early neonatal period
Keywords: вагітність; ситуативна тривожність; стан новонароджених; перинатальні ускладнення; беременность; ситуативная тревожность; состояние новорожденных; перинатальные осложнения; pregnancy; state anxiety; state of newborns; perinatal complications